Is social entrepreneurship better for workers? : The influence of work experience in Croatian social cooperatives on perceived well-being - Puđak, Jelena (Array, 2020)
This paper aims to examine the motivations, values, and job satisfaction among the people employed in the sector of social entrepreneurship that were obtained through a qualitative study of ten Croatian social cooperatives. In our analysis, we interpreted the experiences of working in a social enterprise from the employee perspective. Our findings suggest that the participants/employees of social enterprises favour intrinsic motivation and values related to their jobs, that they describe their working conditions in social enterprises positively, and that they share a perceived increase in the quality of life since having started working at a social enterprise. The described relations between motivation, job experiences, and participatory management allowed us to build upon and extend the existing body of research on motivation and job satisfaction in the social economy sector.